(6+ 2 raiz de 3 /4 + 3 ) * (6 -2 raiz de 3 /4 + 3)
Anexos:
![](https://pt-static.z-dn.net/files/d75/5947db240e22a598e8a3de35a4c41416.png)
Soluções para a tarefa
Respondido por
2
= [(6+2✓3'+12)/4] × [(6-2✓3'+12)/4]
= [(18+2✓3')/4] × [(18-2✓3')/4]
= [(9+✓3')/2] × [(9-✓3')/2]
= (9²-✓3'²)/4
= (81-3)/4
= 78/4
= 39/2 ou 19,5
= [(18+2✓3')/4] × [(18-2✓3')/4]
= [(9+✓3')/2] × [(9-✓3')/2]
= (9²-✓3'²)/4
= (81-3)/4
= 78/4
= 39/2 ou 19,5
nickposeyy:
Muito obrigada
Perguntas interessantes
História,
11 meses atrás
Matemática,
11 meses atrás
Física,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Química,
1 ano atrás
Biologia,
1 ano atrás